2022
DOI: 10.1108/cr-10-2021-0129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk disclosure on the volatility, liquidity and performance of the UK and Canadian insurance companies

Abstract: Purpose This paper aims to investigate the impact of risk disclosure practices (voluntary, mandatory and risk disclosure index) on stock return volatility, market liquidity and financial performance for insurance companies in the UK and Canada, before and after the International Financial Reporting Standards (IFRS) adoption. Design/methodology/approach The panel data analysis covers 14 insurance companies in the UK and 12 in Canada over a six-year period, three years before and three years after the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Overall, the results confirm that convergence with IFRS results in a significant increase in the quantity of risk disclosure. These findings are consistent with previous research (Höring and Gründl, 2011; Kassamany et al , 2021) and support H1 , which posits a positive association between IFRS convergence and increased risk disclosure. The possible reason for this outcome could be the general underlying risk disclosure requirements of IFRS and the strong coercive pressure from regulators brought on by mandatory IFRS convergence (Tauringana and Chithambo, 2016), which collectively serves to encourage firms to provide greater levels of risk-related information in corporate reports.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, the results confirm that convergence with IFRS results in a significant increase in the quantity of risk disclosure. These findings are consistent with previous research (Höring and Gründl, 2011; Kassamany et al , 2021) and support H1 , which posits a positive association between IFRS convergence and increased risk disclosure. The possible reason for this outcome could be the general underlying risk disclosure requirements of IFRS and the strong coercive pressure from regulators brought on by mandatory IFRS convergence (Tauringana and Chithambo, 2016), which collectively serves to encourage firms to provide greater levels of risk-related information in corporate reports.…”
Section: Resultssupporting
confidence: 92%
“…In the current literature, there are two opposing views regarding the impact of IFRS on the extent of risk information disclosures. Proponents argue that IFRS enhances risk disclosure by mandating more detailed and comprehensive risk disclosure requirements (Kassamany et al , 2021; Tauringana and Chithambo, 2016). To be more specific, IFRS 7 and IFRS 9 are designed to encourage disclosure regarding the significance of financial instruments to a firm and the degree of risk originating from those instruments, both in qualitative and quantitative dimensions (Deloitte, 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the three pillars follow heterogeneous patterns (El Khoury et al , 2022a). Kassamany et al (2022) study examined the relationship between risk disclosure practices on stock return volatility, market liquidity and financial performance for insurance companies in the UK and Canada. The results indicated that the compulsory risk disclosure practices positively affect the volatility of stock returns for insurance companies in the UK, but not for Canadian companies.…”
Section: Lecturer and Special Issue Reviewmentioning
confidence: 99%
“…Risk disclosure quality is measured using an index consisting of (50) items that have an equal importance, this index was prepared based on the accounting standards and prior relevant studies (Mokhtar and Mellett, 2013;Martikainen et al, 2015;Kassamany et al,2022).…”
Section: Measuring Risk Disclosure Qualitymentioning
confidence: 99%